2011
DOI: 10.1007/s10753-011-9335-3
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosomal Protein HMGN2 Mediates the LPS-Induced Expression of β-Defensins in Mice

Abstract: Human β-defensin-2 (HBD-2), an antimicrobial peptide produced by epithelial cells, plays an important role in the body's innate and adaptive immunity. High-mobility group N2 (HMGN2), a member of the HMG superfamily, binds to chromatin to modulate gene transcription. Previously, we have shown that HMGN2 acts as a positive modulator of the signal transduction cascade in the process of inducible human β-defensin expression. In our current study, we found that down-regulation of HMGN2 reduces the expression level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…This is consistent with prior reports which observed increases in mBD3 and mBD4 expression in the tongue and stomach of Candida infected mice (39, 40). It was recently discovered that mBD3 and mBD4 upregulation requires the high mobility group nucleosomal binding domain 2 protein (HMGN2), a chromatin binding protein; however, mBD1 expression was shown to be independent of HMGN2, indicating that basal mBD1 expression may be uniquely regulated and a critical component of early mucosal responses (41). We observed a significant reduction in mBD2 and mBD4 expression in DEFB1 −/− mice when compared to WT, demonstrating a possible cross-regulation of these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior reports which observed increases in mBD3 and mBD4 expression in the tongue and stomach of Candida infected mice (39, 40). It was recently discovered that mBD3 and mBD4 upregulation requires the high mobility group nucleosomal binding domain 2 protein (HMGN2), a chromatin binding protein; however, mBD1 expression was shown to be independent of HMGN2, indicating that basal mBD1 expression may be uniquely regulated and a critical component of early mucosal responses (41). We observed a significant reduction in mBD2 and mBD4 expression in DEFB1 −/− mice when compared to WT, demonstrating a possible cross-regulation of these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, we firstly identified HMGN2 functioned as an antimicrobial peptides, and furthermore, we have demonstrated that HMGN2 is a multifunctional protein in immune regulation. For example, we found that HMGN2 promotes LPS‐induced β‐defensin expression in lung epithelial cells . HMGN2 inhibits the internalization of Klebsiella pneumoniae in lung epithelial cell A549 through decreasing the expression and activity of α5β1 integrin and activated FAK‐Src signalling to reduce F‐actin polymerization .…”
Section: Introductionmentioning
confidence: 89%
“…HMGN2 expression is downregulated during the physiological processes of myogenesis, erythrogenesis and chondrogenesis, as well as during embryonic organ formation, such as kidney development (10). Abnormal expression of the HMGN2 gene or protein has been associated with the development of neoplasms and autoimmune diseases (25)(26)(27). However, due to the poorly defined biological functions of this protein, further research is required.…”
Section: Discussionmentioning
confidence: 99%